Komodifkasi Agama dalam Polemik Penentuan Awal Bulan Qamariah di Indonesia - Wildani Hefni (University of Muhammadiyah Sumatera Utara, 2020)
AbstractThis article aims at explaining the ideological political contestation in determining the beginning and end of the qamariah month in Indonesia by using a religious commodification approach. Religious issues that drawn in ideological interest have led to group fanaticism which makes religion as part of commodification in the construct of pragmatic interests. Two paradigms of Hisab and Rukyat become a symbol of differences in determining the beginning and end of the qamariah month in Indonesia. The ideological and political interpretation was born from this debate. In its history, the ideology of socio-religious organization has become a commodity, including in determining the beginning and end of the qamariah month. Nahdlatul and Muhammadiyah carried out commodification by carrying different views of the government’s decision based on their dissatisfaction in determining the beginning and end of the qamariah month. Kata Kunci: Religious commodification, Determination of the Beginning of Qamariyah, NU, Muhammadiyah